2006
DOI: 10.14742/ajet.1284
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding learners in authentic, problem based e-learning environments: The Geography Challenge

Abstract: The affordances of online learning technologies have enabled more widespread development of learning environments that facilitate the exploration and solving of complex and realistic problems. In this paper, we describe the design of a real world geography problem, embedded within a web environment that is facilitated by an onsite excursion for data collection. The learning environment has been designed to deliberately address known problems associated with the problem solving approach, specifically in regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Its school education program incorporates an authentic context for the study of Year 10 geography. In a learning challenge designed to enable students to learn key geography skills (described in detail in Brickell & Herrington, 2006), an authentic context is provided in the form of a brief animation (Figure 1). The park is experiencing problems with mosquitos, smelly ponds and rats attracted by food scraps and other rubbish left by visitors.…”
Section: Example: Sydney Olympic Park Projectmentioning
confidence: 99%
“…Its school education program incorporates an authentic context for the study of Year 10 geography. In a learning challenge designed to enable students to learn key geography skills (described in detail in Brickell & Herrington, 2006), an authentic context is provided in the form of a brief animation (Figure 1). The park is experiencing problems with mosquitos, smelly ponds and rats attracted by food scraps and other rubbish left by visitors.…”
Section: Example: Sydney Olympic Park Projectmentioning
confidence: 99%
“…However selecting or generating problems to promote the kinds of problem solving that Jonassen is advocating is a complex process and has been the focus of much research over the past two decades (Brickell & Herrington, 2006;Hmelo-Silver, 2002). Jonassen (1997Jonassen ( , 2000Jonassen ( , 2011a and others (e.g., Collins, 1991;CTGV, 1993;Hmelo-Silver, 2004;Lundeberg, Levin, & Harrington, 1999;Spiro & Jehng, 1990) have consistently noted that the few problems students encounter in educational contexts are well structured and lack the complexity needed to help students transfer learning to real world problem solving.…”
Section: Introductionmentioning
confidence: 99%
“…While there are several guidelines or frameworks for developing ill-structured problems (e.g., Barrows, 1985;Brickell & Herrington, 2006;Dabbagh & Bannan-Ritland, 2005;Duffy & Cunningham, 1996;Hmelo-Silver, 2002;Jonassen, 1997Jonassen, , 2000Jonassen, , 2011aLesh et al, 2000;Reeves et al, 2002;Schmidt, 1994), research has revealed a high degree of variability across problems used in PBLEs ranging from highly structured problems where context is of secondary concern and the focus is on optimal solutions, to highly ill-structured problems where context is critical and the problem solving process is valued more than the problem solution (Jonassen, 2000;Walker & Leary, 2009). Hence, this study sought to examine the specific characteristics of problems used in PBLEs in order to better inform the selection and generation of ill-structured problems for teaching and learning contexts.…”
Section: Introductionmentioning
confidence: 99%
“…If students are equipped with the ability to grasp the key points of the problems, they may be able to seek efficiently what they need from the Internet with appropriate keywords, and then extract content effectively from the searched results. On the contrary, if they fail to identify the key points of the problem, the whole problem solving process is likely to be inefficient (Pharo & Jarvelin, 2004;Wormeli, 2005;Brickell & Herrington, 2006;Tu, Shih & Tsai, 2008;Susar & Akkaya, 2009;Antiqueira, Oliveira, Costa & Nunes, 2009;Veletsianos & Doering, 2010). Hence, this study attempts to employ an information summarising instruction strategy to enhance the information comprehension and summarising abilities of the students; hopefully, their web-based problem solving ability can be improved as well.…”
Section: Literature Reviewmentioning
confidence: 99%